IFT proteins interact with HSET to promote supernumerary centrosome clustering in mitosis. (9th April 2020) - Vitre, Benjamin; Taulet, Nicolas; Guesdon, Audrey; Douanier, Audrey; Dosdane, Aurelie; Cisneros, Melanie; Maurin, Justine; Hettinger, Sabrina; Anguille, Christelle; Taschner, Michael; Lorentzen, Esben; Delaval, Benedicte
Abstract: Centrosome amplification is a hallmark of cancer, and centrosome clustering is essential for cancer cell survival. The mitotic kinesin HSET is an essential contributor to this process. Recent studies have highlighted novel functions for intraflagellar transport (IFT) proteins in regulating motors and mitotic processes. Here, using siRNA knock‐down of various IFT proteins or AID‐inducible degradation of endogenous IFT88 in combination with small‐molecule inhibition of HSET, we show that IFT proteins together with HSET are required for efficient centrosome clustering. We identify a direct interaction between the kinesin HSET and IFT proteins, and we define how IFT proteins contribute to clustering dynamics during mitosis using high‐resolution live imaging of centrosomes. Finally, we demonstrate the requirement of IFT88 for efficient centrosome clustering in a variety of cancer cell lines naturally harboring supernumerary centrosomes and its importance for cancer cell proliferation. Overall, our data unravel a novel role for the IFT machinery in centrosome clustering during mitosis in cells harboring supernumerary centrosomes. Synopsis: Cancer cells with centrosome amplification cluster their centrosomes to form bipolar mitotic spindles. This study reveals that intraflagellar transport (IFT) proteins are required for centrosome clustering in mitosis by interacting with the kinesin HSET. Depleting IFT52 or IFT88 interferes with centrosome clustering. IFT complex mediates centrosome clustering by directly interacting with the kinesin HSET. IFT88 depletion reduces HSET turnover on mitotic spindle microtubules. IFT52 depletion reduces centrosome clustering dynamics in late G2 and mitosis. Depletion of IFT88 in cancer cells exhibiting centrosome amplification leads to reduced proliferation and survival. Abstract : Cancer cells with centrosome amplification cluster their centrosomes to form bipolar mitotic spindles. This study reveals that intraflagellar transport (IFT) proteins are required for centrosome clustering in mitosis by interacting with the kinesin HSET.